Errors in the written English of native users of sign language: An exploratory case study of Hong Kong deaf students. (June 2016) - Thierfelder, Philip; Stapleton, Paul
Abstract: A considerable amount of research has been performed on the English writing of native Cantonese speaking students from mainstream school settings in Hong Kong. However, there have been few studies on the English writing of their deaf counterparts. The present exploratory study investigates the English writing of deaf learners who use Hong Kong Sign Language (HKSL) as their primary mode of communication. Via an analysis of errors found in essays written by five deaf English learners who are primary users of HKSL, we found that the most common errors were in their choice of words and in their use of articles and plural markings. Many of these errors appeared to be a result of transfer from HKSL, although some errors occurred via interaction between the learners' HKSL and their written Chinese, which was the second language of the participants. The pedagogical implications of this transfer and interaction in the learning of English are discussed.